Clinical and histological findings of autosomal dominant renal‐limited disease with LMX1B mutation. Issue 9 (September 2016) - Konomoto, Takao; Imamura, Hideaki; Orita, Mayuko; Tanaka, Etsuko; Moritake, Hiroshi; Sato, Yuji; Fujimoto, Shouichi; Harita, Yutaka; Hisano, Satoshi; Yoshiura, Koh‐ichiro; Nunoi, Hiroyuki
Abstract: Aim: Mutations of LMX1B cause nail‐patella syndrome, a rare autosomal dominant disorder. Recently, LMX1B R246Q heterozygous mutations were recognised in nephropathy without extrarenal manifestation. The aim of this study was to clarify characteristics of nephropathy caused by R246Q mutation. Methods: Whole exome sequencing was performed on a large family with nonsyndromic autosomal dominant nephropathy without extrarenal manifestation. Clinical and histological findings of patients with LMX1B mutation were investigated. Results: LMX1B R246Q heterozygous mutation was identified in five patients over three generations. Proteinuria or haematoproteinuria was recognized by urinary screening from all patients in childhood. Proteinuria gradually increased to nephrotic levels and renal function decreased in adolescence. Two patients progressed to end‐stage renal disease in adulthood. Renal histology demonstrated minimal change in childhood and focal segmental glomerulosclerosis in adulthood. Using electron microscopy, focal collagen deposition could be detected in glomeruli even when a "moth‐eaten appearance" was not apparent in the glomerular basement membrane. In addition, podocin expression in glomerular podocytes was significantly decreased, even in the early stages of disease progression. Conclusion: Comprehensive genetic analyses and collagen or tannic acid staining may be useful for diagnosis of LMX1B ‐associated nephropathy. While renal prognosis of R246Q may be worse than that of typical NPS nephropathy, signs of podocytopathy can be detected during the infantile period; thus, childhood urinary screening may facilitate early detection. SUMMARY AT A GLANCE: LMX1B mutations known to cause nail‐patella syndrome were recently identified in patients with nail‐patella‐like disease and in patients with herediary FSGS without extrarenal manifestation. Thus, LMX1B‐associated nephropagy has received increasing attention, but clinical features and kidney histologies remains uncertain in these patients. This manuscript provide meanigful information on the LMX1B‐associated nephropagy.